Analisis Kontribusi Pajak Daerah terhadap Pendapatan Asli Daerah Kabupaten Nganjuk - Hadi Sutrisno; Junaedi Junaedi; Anik Ekowati (Journal of Public Power, 2023)
This study aims to analyze the contribution and optimization of local taxes in increasing Regional Original Revenue (PAD) in Nganjuk Regency. The study applies a descriptive quantitative approach by using secondary data on PAD realization and local tax revenues during 2016-2020, supported by interviews and documentation at the local revenue office. The results indicate that PAD increased nominally from Rp323.04 billion in 2016 to Rp403.08 billion in 2020, but the contribution of PAD to total regional income remained relatively low, indicating that fiscal independence has not been fully achieved. Local taxes became the most strategic PAD component after other legitimate PAD, with an average contribution of 25.64% to PAD and an average growth of 12.13% per year. The dominant local taxes were PBB-P2, street lighting tax, and BPHTB, while several taxes such as entertainment tax, parking tax, groundwater tax, and mineral tax contributed relatively small and fluctuating amounts. Optimization requires integrated intensification and extensification through data updating, digital transaction monitoring, taxpayer education, institutional coordination, and stronger supervision. The study concludes that strengthening local tax governance, transparency, and accountability is essential to build sustainable regional fiscal independence